2018
DOI: 10.1111/jocn.14556
|View full text |Cite
|
Sign up to set email alerts
|

Factors that have an impact on knowledge, attitude and practice related to kangaroo care: National survey study among neonatal nurses

Abstract: Neonatal nurses' knowledge and belief need to be improved for optimal practice of kangaroo care. Organisational support and clear guidelines are also in need for successful kangaroo care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 58 publications
4
35
0
3
Order By: Relevance
“…These are present conditions of our NICUs while family centered care is currently considered as a caring philosophy in which cooperation between nurses and families is of prime importance; this composes functional basis for this philosophy. However, in certain conditions, type of designing and environment allocated to neonatal intensive care unit should not influence efficacy and success of family-centered care on families, infants, and nurses (13,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…These are present conditions of our NICUs while family centered care is currently considered as a caring philosophy in which cooperation between nurses and families is of prime importance; this composes functional basis for this philosophy. However, in certain conditions, type of designing and environment allocated to neonatal intensive care unit should not influence efficacy and success of family-centered care on families, infants, and nurses (13,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…In multiple studies, researchers explored the facilitators and barriers to implementation of SSC in the NICU, and the results are fairly consistent across studies. Nurses have described the need for education about SSC and training on SSC transfer techniques, as well as development and implementation of evidence-based policies and procedures (Deng, Zhang, Li, Wang, & Xu, 2018;Engler et al, 2002;Strand, Blomqvist, Gradin, & Nyqvist, 2014).…”
Section: Implications For Nursing Practicementioning
confidence: 99%
“…However, the study by Abdulkarimi et al [27] showed that pregnant mothers did not have a good attitude toward taking care of their newborns due to being addicted, which is not consistent with the ndings of the present study. The studies by Salem in Saudi Arabia [24], Deng in China [28] and Chia in Melbourne [29] assessed nurses' attitudes toward newborn care as low or average. The reasons can be the staff's heavy workload, insu cient education, lack of organizational support and lack of transparent protocols, especially for low birth weight babies.…”
Section: Discussionmentioning
confidence: 99%